IMPLEMENTASI SISTEM KEUANGAN DESA (SISKEUDES) PADA PEMERINTAHAN GAMPONG BLANG NEUANG KECAMATAN BEUTONG KABUPATEN NAGAN RAYA - Nila Trisna; Reli Wahyuni (Prodi Ilmu Hukum, Universitas Teuku Umar, 2019)
The application is aimed at village government officials to facilitate the management of Village Finance. This study uses normative juridical methods and Empirical Juridical This study uses normative legal research methods. The research material is analyzed with a qualitative approach, with the aim of understanding the meaning of the collected legal material, which is then interpreted normatively, logically and systematically by using the inductive method. In the implementation of the Village Financial System Application (SISKEUDES) there are still constraints on how to collect data on the siskeudes. So that the implementation of the Village Financial System Application (SISKEUDES) has not proceeded as expected by the Statutory Regulations. Keywords: Implementation, siskeudes, Gampong government